Pengaruh Brand Ambassador, Product Image, Cita Rasa dan Harga Terhadap Keputusan Pembelian Mie Sedaap Korean Spicy - Putra, Herosonita Bambang Damori Yoga Swarna Weswaning Ramadhan Tjarata; Sonani, Nia; Yulia, Iis Anisa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze the influence of Brand Ambassador, Product Image, Taste and Price on the Purchase Decision of Korean Spicy Mie Sedaap. The sample used in this study had 150 respondents. The analytical method used is multiple linear regression with the dependent variable being the purchase decision, and the independent variables being Brand Ambassador, Product Image, Taste and Price. The results of the study show that the price partially has no effect on the Purchase Decision, Brand Ambassador, Product Image, and Taste have a partial effect on the Purchase Decision. Variables Brand Ambassador, Product Image, Taste and Price simultaneously influence Purchase Decisions. Of the three independent variables that have an influence, the Product Image variable has the greatest influence on Purchasing Decisions.